Why is manganese so valuable to bacterial pathogens? - Čapek, Jan; Večerek, Branislav (Frontiers in Cellular and Infection Microbiology, 2023)
Apart from oxygenic photosynthesis, the extent of manganese utilization in bacteria varies from species to species and also appears to depend on external conditions. This observation is in striking contrast to iron, which is similar to manganese but essential for the vast majority of bacteria. To adequately explain the role of manganese in pathogens, we first present in this review that the accumulation of molecular oxygen in the Earth’s atmosphere was a key event that linked manganese utilization to iron utilization and put pressure on the use of manganese in general. We devote a large part of our contribution to explanation of how molecular oxygen interferes with iron so that it enhances oxidative stress in cells, and how bacteria have learned to control the concentration of free iron in the cytosol. The functioning of iron in the presence of molecular oxygen serves as a springboard for a fundamental understanding of why manganese is so valued by bacterial pathogens. The bulk of this review addresses how manganese can replace iron in enzymes. Redox-active enzymes must cope with the higher redox potential of manganese compared to iron. Therefore, specific manganese-dependent isoenzymes have evolved that either lower the redox potential of the bound metal or use a stronger oxidant. In contrast, redox-inactive enzymes can exchange the metal directly within the individual active site, so no isoenzymes are required. It appears that in the physiological context, only redox-inactive mononuclear or dinuclear enzymes are capable of replacing iron with manganese within the same active site. In both cases, cytosolic conditions play an important role in the selection of the metal used. In conclusion, we summarize both well-characterized and less-studied mechanisms of the tug-of-war for manganese between host and pathogen.